Optimization Design Blade Wind Turbine in Enhancing Power Based on Passive Control System - I Kade Wiratama; I Gusti Ngurah Ketut Yudhyadi; I Made Suartika; I Made Nuarsa (Postgraduate, University of Mataram, 2023)
Control power on rotor wind turbine can be carried out by changing blade angle of attack through via pitch control and stall regulated method to produce much power and control power as well as protect wind turbine from high wind to operate in rated power. By using search-based design method to optimize design blade and Blade Element Momentum Theory (BEMT) to analyze aerodynamic performance for stall and pitch control power. Recent work demonstrates that some very significant effect can be achieved by using constant speed pitch control. Comparing of among ordinary blade and design blade of constant speed stall regulated and optimized show that enhancing power is nearly similar while design blade using pitch control give significant effect in enhancing aerodynamic performance of design blade. For average power, design blade constant speed pitch control has average power about 47970,77 Watt and constant speed stall regulated is 43855,41 Watt